2015
DOI: 10.1007/s11156-015-0528-y
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy and the US stock market

Abstract: This paper empirically explores the short-and long-run effects of fiscal and monetary policies on US stock returns and tests the validity of market efficiency. The results support the presence of a strong long-run (equilibrium) relation binding stock prices with fiscal (but not monetary) policy. Further tests assign a dominant role to fiscal policy as a main force driving the overall equilibrium relation with the stock market. Estimates from error-correction models corroborate the existence of robust long-run … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…As our analyses confirm, both economies still have the space to improve the role of their governments in promotion and in real support of R&D. More systemic, as well as addressed, approach in the financing of innovations is required. We agree with the previous authors, for example Mbanga andDarrat (2016, pp. 987-1002) and Laird (2020) that it is a long-term process.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As our analyses confirm, both economies still have the space to improve the role of their governments in promotion and in real support of R&D. More systemic, as well as addressed, approach in the financing of innovations is required. We agree with the previous authors, for example Mbanga andDarrat (2016, pp. 987-1002) and Laird (2020) that it is a long-term process.…”
Section: Discussionsupporting
confidence: 94%
“…A special part of this research pays attention to the relationship between fiscal expenditures and the stock markets. For example, according to Mbanga andDarrat (2016, pp. 987-1002), there are longterm and short-term effects of fiscal policy on American stock markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the study indicated that with the increase in the investor knowledge more people are beginning to understand and consider the news relating to the fiscal policies for formulation their decisions. The study by Mbanga and Darrat (2016) evaluated the long run and short run effects of the monetary and fiscal policies on the returns of the stock market and evaluated the efficiency of the of the market. The results indicated the presence of a long run equilibrium relation present among the fiscal policy and the stock prices.…”
Section: Discussionmentioning
confidence: 99%
“…However, in economics and market settings, fiscal policy and rules are the adoptions of government earnings collection such as taxes and other and spending to impact the nation's stock market. According to Mbanga and Darrat (2016) the use of government revenues as well as expenditures to affect macro-economic factors generated as a consequence of the depression majorly when the past approaches to market became unfamiliar. Prukumpai and Sethapramote (2019) in his research described that FP is mainly based on different economic theories and models that speculate that national administration modifications in the equate of tariff and also SP impacts aggregate need and the degree of market action (Ito, Noda, & Wada, 2016).…”
Section: The Relationship Between Fiscal Policy and Stock Market Pricmentioning
confidence: 99%
“…Drugi autori istražuju povezanost izme u navedenih varijabli u kontekstu tržišne eÞ kasnosti (Barbi & ondi -Jurki , 2011;Mbanga & Darrat, 2016). Stupanj eÞ kasnosti tržišta kapitala ovisi o brzini i to nosti kojom su informacije ugra ene u cijene dionica.…”
Section: Uvodunclassified